2020
DOI: 10.1063/5.0005576
|View full text |Cite
|
Sign up to set email alerts
|

Sheath potential coefficient in plasma with nonextensive distribution

Abstract: Theoretical analysis and a large number of experiments have proved that plasma components do not satisfy Boltzmann–Gibbs statistics and can be well described by nonextensive statistical mechanics, while sheath potential coefficients in plasma with nonextensive distribution are not investigated deeply and comprehensively. Here, we investigate the ion sheath formed around a nonextensive single electric probe in plasma described by nonextensive statistical mechanics, and find that the sheath potential coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recent studies 1 have shown that replacing Boltzmann–Gibbs statistical mechanics with nonextensive statistical mechanics has a strong advantage in describing plasmas. The diagnosis error without using nonextensive statistical mechanics to describe the plasma may be as high as 4 . We established the theory of nonextensive geodesic acoustic mode by introducing nonextensive statistical mechanics to take into account the system nonextensivity which has been proven by a large number of facts 3 , 12 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies 1 have shown that replacing Boltzmann–Gibbs statistical mechanics with nonextensive statistical mechanics has a strong advantage in describing plasmas. The diagnosis error without using nonextensive statistical mechanics to describe the plasma may be as high as 4 . We established the theory of nonextensive geodesic acoustic mode by introducing nonextensive statistical mechanics to take into account the system nonextensivity which has been proven by a large number of facts 3 , 12 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The consideration of nonextensivity effects is very important to the accurate diagnosis of plasma parameters. When the nonextensivity effects are not considered, the diagnosis error of the electric probe may be as high as 83.91% 4 . Therefore, we must consider the influence of nonextensive parameters and the measurement of the nonextensive parameters is a must.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This failure of the Boltzmann-Gibbs statistics is supported by many theoretical results [21][22][23] and a large number of experiments. [24][25][26][27] Many works show that the behaviour of the plasma electrons can be well described by q-non-extensive statistical mechanics, [28,29] proposed by Tsallis. The BG entropy can be recovered from Tsallis entropy in the limit of q → 1.…”
Section: Introductionmentioning
confidence: 99%